Seedling Growth and Systemic Uptake of Liquid Vermicompost-Coated Seeds in Organic Pumpkin (Cucurbita sp.) - Wissanee Pola; Sukanya Aiamla-or (Horticulturae)
Liquid vermicompost (LVC) is one of the organic ingredients for improving plant growth. This study aims to investigate the impact of the application of LVC coating formulations in distinct ratios on seeding emergence, seedling growth parameters, and nitrogen content as well as the systemic uptake characteristics in seedlings. Coating formulations contained gum arabic (GA) mixed with 5–15% of LVC and were applied to pumpkin seeds and compared to non-coated seeds. All samples were stored under cold and ambient conditions for 3 months to evaluate the performance of the coating. Results showed no statistical distinctions in the percentage of seedling emergence. Nevertheless, the 5LVC-GA in the organic formulation significantly increased shoot length, seedling growth rate (SGR), seedling vigor index (SVI), and nitrogen content (%) in the coated seedlings. Additionally, the evaluation of seedling uptake was achieved using rhodamine B as a fluorescent tracer which was diluted in the organic formulation. This explored the transportation of the treatment within a seedling. Therefore, the application of an optimum concentration of 5LVC-GA treatment can improve seedling growth and nitrogen accumulation. This could be confirmed with fluorescence imaging of translocation to seedling organs. However, seed storability declines over three months, emphasizing the need for better coatings and packaging solutions.